2021
DOI: 10.3390/children8121080
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Experiential School-Based Culinary Interventions for 5–12-Year-Old Children

Abstract: Cooking is an essential skill and the acquisition of cooking skills at an early age is associated with higher diet quality. This review aimed to describe the characteristics of school-based experiential culinary interventions and to determine the value of these to child (5–12 years) health outcomes. Interventions were eligible for inclusion if they took place in school during school hours, included ≥3 classes, and had a control group. Interventions published up to May 2021 were included. The databases searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A meta-analysis found that an effective strategy for facilitating healthy eating among primary school children enhances experiential learning (Dudley et al, 2015). A literature review showed that school-based experiential cookery interventions may impact health-related aspects among children positively (Bennett et al, 2021). Increasing opportunities to cook and to be involved in meal preparation may therefore be an effective strategy because it can facilitate healthy eating habits among students with low interest in that area.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that an effective strategy for facilitating healthy eating among primary school children enhances experiential learning (Dudley et al, 2015). A literature review showed that school-based experiential cookery interventions may impact health-related aspects among children positively (Bennett et al, 2021). Increasing opportunities to cook and to be involved in meal preparation may therefore be an effective strategy because it can facilitate healthy eating habits among students with low interest in that area.…”
Section: Discussionmentioning
confidence: 99%
“…Searches were limited to articles published in the English language and peer‐reviewed journal articles. The pragmatic approach that supported the database searching utilised four relatively recently published reviews on varying aspects/outcomes of children's cooking interventions (Bennett et al, 2021; Hasan et al, 2019; Hersch et al, 2014; Ng et al, 2021); these reviews provided an initial outline of 50 articles relating to children's cooking interventions. All articles were screened initially using titles for relevancy and duplication.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the increase in interventions in recent years, it is essential to understand their effectiveness and whether there have been methodological improvements so that effective interventions could be implemented widely. More recent reviews have focused on cooking classes and multicomponent interventions (Hasan et al, 2019), school‐based interventions (Bennett et al, 2021) and hands‐on practical preparation (Ng et al, 2021), and on mainly nutrition and food‐based outcomes. Therefore, this review aimed to undertake an investigation of the different methodological approaches used in a broad range of children's culinary nutrition interventions and experiments.…”
Section: Introductionmentioning
confidence: 99%
“… 83–86 Children who enjoy the experience of shared family mealtimes are reported to be more positive about trying new foods in a nonmodeling context. 71 , 87 , 88 In addition, research found that young adults’ present commensality is positively associated with their recalled frequencies of childhood family meals. 89 In the same study, recalling mothers’ home cooking during childhood was also a significant predictor of young adults’ cooking for themselves in the present day.…”
Section: Development Of Food Literacy In Children and Adolescentsmentioning
confidence: 99%
“… 145 Culinary interventions in the school setting have been associated with improvement in cooking skills, healthier eating habits, and positive changes in anthropometric measurements. 88 , 146 However, the optimal age to acquire and retain different types of food preparation skills is still unknown. 20 …”
Section: Development Of Food Literacy In Children and Adolescentsmentioning
confidence: 99%